The influence of Reestablishment of Occlusal Vertical Dimension in One step or gradually on aesthetic and functional Aspects in Edentulous - ميا هبه; محمود محمود (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Treating Edentulous patients constitutes meticulousness by general dentists due to the challenges faced in imitating the previous state of the patient, and among these challenges is the restoration of symmetry and harmony of the face. The crucial factor on which this mechanism is based is in the lower third of the face is the occlusal vertical dimension. Aim: A study of the resulting changes in the aesthetic appearance of edentulous patients upon the gradual increasing of the vertical dimension in comparison with the direct increasing of the occlusal vertical dimension. Method: The research sample included 30 patients who were divided into two groups, each group included 15 patients. The gradual increase was performed on the first group and the direct increase on the second group. Optical pictures of the patients in two groups before and after the end of treatment were taken, and later presented to three groups of investigators. The investigators answered a questionnaire on the basic aesthetic points. Results: The results of the statistical analysis showed the superiority of the Direct increasing technique compared to the Gradual increasing technique in terms of its effect on the aesthetic aspects, especially in terms of the position of the chin and lip. Conclusions: The direct increasing technique gave better results in terms of aesthetics than the gradual increasing technique.